Special features of dolichognathic dental arches in people with teeth size variations - D. A. Domenyuk; E. G. Vedeshina; S. V. Dmitrienko (Кубанский научный медицинский вестник, 2016)
The work offers a view on the results obtained from a study involving 253 patients of both sexes in the first period of their adulthood who had physiological occlusion of permanent teeth and dolichognathic (i. e. elongated in the sagittal direction) dental arches. It was found that in patients with dolichognathic normodontia as well as macrodontia the angles of vestibular-lingual inclination matched high torque braces. Patients with dolichognathic microdontia had their angles of vestibular-lingual inclination close to standard torque braces. The angulation angles in cases with dolichognathic shape of dental arches revealed virtually no dependence on the size of the permanent teeth, whereas the difference in these indicators was not statistically significant.